Validity and Practicality: Development of an Interactive Flipbook to Enhance Students Knowledge and Digital Literacy - Hadi, Achmad Syaiful; Rahayu, Sri Endarti; Saputro, Budiyono (Journal of Natural Science and Integration, 2025)
The 21st century increases competitiveness by requiring students to have various skills. Technology and learning media are very important to support the learning process. However, without new innovations in the use of this learning media, students will not achieve learning goals and master the skills needed. The purpose of this study is to design and develop interactive learning media in the form of flipbooks to improve students understanding and digital literacy on the classification of living things, Plantae sub-material, Angiosperm sub-division, especially about the types of medicinal plants used by the Betawi Ciracas people. It also aims to provide new knowledge with interactive digital learning media, so that it can be used while learning. The results of this research are in the form of an interactive flipbook named "Intobamaskutaras" (Intervarisasi tanaman obat masyarakat suku Betawi Ciracas). The methodology of this research is research and development using the ADDIE model, among others; Analyze, design, develop, implement, and evaluate. Data collection techniques are in the form of observations, interviews and questionnaires. The subjects in this study involved 10 students as the initial trial subject, and 36 students as the subject of the use trial. Based on the results of the validation of material experts, 90.83%, and media experts, of 91.36%, are included in the very good or very valid category. In terms of usability, it obtained an assessment percentage of 97.75% from the results of the response of teachers and students to the practicality of flipbooks. This shows that the beneficial aspect of this flipbook is very practical.Keywords: ethnobotany, flipbook, medicinal plants, research and development.